Bilingual Android App for Early Nutrition Education - Oktariani, Falinda; Erowati, Dewi; Rahmatullah, Muhammad Nufus (JURNAL PROTEKSI KESEHATAN, 2024)
This study investigates the implementation and effectiveness of NutriPlay, an Android-based application designed to enhance understanding of balanced nutrition among early childhood students in Pekanbaru, Indonesia. NutriPlay features interactive, visually engaging, and bilingual content aimed at enriching children’s vocabulary while promoting nutrition education. The study involved 30 students from PAUD Lily Jaya and PAUD Al-Fatah, with data collected on usage duration, interest level, ease of use, and improvement in nutrition understanding. The results indicate that 70% of the students used NutriPlay for less than 5 minutes per session, while 30% used it for 5-10 minutes per session, and none of the students used it for more than 10 minutes. Despite the short usage periods, 85% of the students reported increased interest in the application, and 90% showed significant improvement in their understanding of nutrition concepts. These findings suggest that NutriPlay is effective in delivering educational content within short usage periods, sustaining children’s interest through repeated use, and significantly improving their understanding of nutrition concepts.